2016
DOI: 10.3329/bjar.v40i4.26929
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic variations in growth, yield and yield components of soybean genotypes under drought stress conditions

Abstract: A pot experiment was carried out in a venylhouse at Bangabandhu Sheikh Mujibur Rahman University during 2012 to investigate the growth, yield and yield contributing characters of ten selected soybean genotypes viz. Shohag, BARI Soybean-6, BARI Soybean-5, BD2331, BD2329, BD2336, BD 2340, BGM2093, G00015 and BGM2026 under drought stress and control conditions. Plant height, number of leaves, leaf area, shoot and root dry weight of all the genotypes were significantly affected by the stress. Among the genotypes S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…All these causes disturbance in the assimilation mechanism that is directly involved in better growth and yielding. These results are similar with the findings of Anyia and Herzog (2004) and Chowdhury et al (2015), who observed decrease in plant biomass of cowpea underwater deficit throughout the experimental periods. The findings of this study are comparable with the study of Ashraf and Ashraf (2012); Orabi et al ( 2018), who reported a drought-triggered reduction in biomass production of maize and canola.…”
Section: Discussionsupporting
confidence: 92%
“…All these causes disturbance in the assimilation mechanism that is directly involved in better growth and yielding. These results are similar with the findings of Anyia and Herzog (2004) and Chowdhury et al (2015), who observed decrease in plant biomass of cowpea underwater deficit throughout the experimental periods. The findings of this study are comparable with the study of Ashraf and Ashraf (2012); Orabi et al ( 2018), who reported a drought-triggered reduction in biomass production of maize and canola.…”
Section: Discussionsupporting
confidence: 92%
“…Plants are unable to maintain metabolic activities, especially the turgidity of cell for normal growth under salt or water stress conditions, and that finally resulted yield reduction (Khan et al, 2016). Salinity or water shortage decreased pod number in pea (Duzdemir et al, 2009) and soybean (Chowdhury et al, 2015). Soybean is classified as a moderately salt sensitive crop (Katerji et al, 2003) and denoted as sensitive to drought stress, especially at the early reproductive stage (Westgate and Peterson, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Drought stress at reproductive stage reduced the soybean yield from 40 to 68% [1], [2], depends on August. This showed that the research took place in dry conditions even when the plants were in the reproductive stage.…”
Section: Introductionmentioning
confidence: 99%